High erector spinae endurance reduced low back pain in postmenopausal women - Rachmawati, Maria Regina (Faculty of Medicine, Trisakti University, 2011)
Low back pain (LBP) is the most frequent health problem in all age groups, including postmenopausal women, who are at risk of disability, due to degenerative processes affecting all organ systems, including the erector spinae muscles. In addition, postmenopausal women also experience a decrease in esterogen levels, which stimulates osteoclastic activity and initiates a reduction in bone mineral density (BMD). The aims of the present study were to determine the relationship between LBP prevalence and erector spinae endurance, BMD reduction, and body mass index (BMI) respectively. This was a cross-sectional study, conducted on 213 postmenopausal women, selected by simple random sampling. Assessment of pain, expressed on a visual analog scale (VAS), was performed by interviews and measurement of erector spinae muscle endurance time using a modified Biering-Sorensen technique, while BMD was assessed by bone densitometry. The results of the study showed that the postmenopausal women had a mean age of 53.5 Â± 3.6 years. The prevalence of LBP and osteoporosis in the postmenopausal women was 58.2% and 21.6%, respectively. A significant positive linear correlation was found between BMI and VAS (r=0.165; p=0.016). In addition, the t-test demonstrated a significant difference in mean VAS scores between good and poor erector spinae endurance (p=0.008). However, the chi-square test showed no significant relationship between reduced BMD and LBP (p>0.05). It is recommended that low back pain in postmenopausal women be managed by strengthening exercises of the erector spinae.